Genetic polymorphisms of Ca2+ transport proteins and molecular chaperones in mitochondria-associated endoplasmic reticulum membrane and non-alcoholic fatty liver disease - Tang, Zongzhe; Ding, Yajie; Zhang, Ru; Zhang, Mengting; Guan, Qing; Zhang, Liuxin; Wang, Hongliang; Chen, Yue; Jiang, Rong; Zhang, Wei; Wang, Jie (Frontiers in Endocrinology, 2023)
Background: Non-alcoholic fatty liver disease (NAFLD) is recognized to be closely associated with endoplasmic reticulum stress and mitochondrial dysfunction, while previous studies have emphasized the important role of calcium homeostasis from the mitochondria-associated endoplasmic reticulum membrane (MAM) in the endoplasmic reticulum and mitochondria. This article will assess the association between genetic polymorphisms of Ca2+ transport proteins and molecular chaperones in MAM and NAFLD risk. Methods: A case-control study was conducted in a community of Nanjing, China during April to December 2020. 2701 subjects were enrolled and genotyped for 6 genetic variants in HSPA5 and ITPR2 genes. Logistic regression analysis was used to assess impact of these variants on NAFLD risk. Results: After adjusting for age, gender, total cholesterol and glucose, we identified that HSPA5 rs12009 variant genotypes (recessive model: OR= 0.801, 95% CI= 0.652-0.986, P= 0.036), rs430397 variant genotypes (recessive model: OR= 0.546, 95% CI= 0.314-0.950, P= 0.032), and ITPR2 rs11048570 variant genotypes (recessive model: OR= 0.673, 95% CI= 0.453-0.999, P= 0.049) were associated with a reduced risk of NAFLD. Multivariate stepwise regression analysis indicated that gender, glucose, body mass index, triglycerides and favorable alleles were independent influencers of NAFLD (all P< 0.05). The area under the receiver operating characteristic curve was 0.764 (95% CI= 0.745-0.783, P< 0.001). Conclusion: The variant genotypes of Ca2+ transport-associated genes HSPA5 (rs12009 and rs430397) and ITPR2 (rs11048570) might contribute to the reduction of the NAFLD risk in Chinese Han population, which can provide new insight into NAFLD pathogenesis.